McLuhan’s Warning, Frye’s Strategy, Emerson’s Dream - Rich Murphy (Journal of the Assembly for Expanded Perspectives on Learning, 2006)
McLuhan's Warning, Frye's Strategy, Emerson's Dream argues the vital function of literary writing in the academy. The essay maps a road from the warnings of catastrophe by Marshall McLuhan to Emerson's dream of all American citizens being poets through the writing strategies of Northrop Frye. It is argued that what one learns through literary writing is especially important during the crises that are ongoing in the West.